Process Monitoring of Village Health and Nutrition Days (Mamta Days) In Navsari District, Gujarat, India - Bharatkumar H. Patel; Monark Jitendra Vyas (Medsci Publications, 2019)
Background: Village Health and Nutrition Day (VHND) identified as an important tool to provide a unique platform at village level to deliver health and nutrition services to RMNCH+A programme beneficiaries. Objectives: (1) to assess the availability of logistics and supplies at VHNDs and (2) to monitor the process of services at VHNDs. Method: It was a cross-sectional study, in which 15 VHNDs selected from Navsari district by multi-stage random sampling method. Out of total 15 planned visits, 14 completed in a calendar year. Data analyzed using MS Excel software. Results: All VHND sessions visited were as per the microplan, equipped with key staff , logistics and supplies like weighing scale, mamta card, and growth chart, vaccines (except BCG- not available at 20% sites), medicines and supplements were available at all sites. BP instrument, thermometer, hemoglobinometer and uristrix strips were available at 70-90% sessions. Immunization and growth monitoring, two main services of VHND were satisfactory at all sites. Skill of blood pressure measurement and Hb estimation was satisfactory where it was available. However, antenatal examination, nutrition counselling, family planning counselling and supportive supervision were deficient at majority sites.